2019
DOI: 10.1080/21505594.2019.1682752
|View full text |Cite
|
Sign up to set email alerts
|

H-NS is the major repressor of Salmonella Typhimurium Pef fimbriae expression

Abstract: Fimbriae play an important role in adhesion and are therefore essential for the interaction of bacteria with the environments they encounter. Most of them are expressed in vivo but not in vitro, thus making difficult the full characterization of these fimbriae. Here, we characterized the silencing of plasmid-encoded fimbriae (Pef) expression, encoded by the pef operon, in the worldwide pathogen Salmonella Typhimurium. We demonstrated that the nucleoid-associated proteins H-NS and Hha, and their respective para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 71 publications
(136 reference statements)
0
13
0
Order By: Relevance
“…From those, Pef is reported to be expressed in static conditions and an acidic medium [36]. T1F expression has been reported to prevent the expression of Pef [37]; therefore, a lack of T1F may induce Pef expression.…”
Section: Discussionmentioning
confidence: 99%
“…From those, Pef is reported to be expressed in static conditions and an acidic medium [36]. T1F expression has been reported to prevent the expression of Pef [37]; therefore, a lack of T1F may induce Pef expression.…”
Section: Discussionmentioning
confidence: 99%
“…To identify foreign genes, the H-NS system recognizes a prokaryotic AT-hook DNA binding motif, which is preferentially inserted into DNA sequences rich in AT pairs [152]. Thus, these proteins bind the newly acquired sequence and prevent the potentially harmful effects of their uncontrolled expression [151,153]. In macrophages, S. enterica degrades H-NS allowing the expression of HGT.…”
Section: The Histone-like Protein Family (H-ns)mentioning
confidence: 99%
“…Conservation in amino acid sequences of both the Lon protease and in the H-NS itself suggests that gut microflora have a shared, discovered strategy of expression of alien genes suppressed by H-NS. The H-NS is protected before Lon when it is bound to DNA [ 153 ].…”
Section: Molecular Systems Of Multiple Resistance In Salmonellamentioning
confidence: 99%
“…was associated with preferential binding to cell lines representing the host that the serovar was isolated from (e.g., Dublin and bovine cells) ( Yue et al, 2015 ), corroborating the results of previous studies that suggested that different fimH alleles allowed for selective binding to different host cell types ( Boddicker et al, 2002 ; Kisiela et al, 2012 ; Grzymajło et al, 2013 ). Last, fimbrial gene expression is a complex process that involves regulators encoded in the fimbrial gene cluster that directly regulate transcription of genes in the cluster ( Kolenda et al, 2019 ), as well as global regulators including H-NS ( Hurtado-Escobar et al, 2019 ), CsrA ( Sterzenbach et al, 2013 ), and HdfR ( García-Pastor et al, 2019 ). These complex regulatory pathways may also partially explain why strains representing different serovars show variable expression of fimbriae, and why deletion of these chaperone-usher fimbrial gene clusters in has varying effects on influencing virulence ( Azriel et al, 2017 ).…”
Section: Making An Entrance—examining a Role For Chaperon-usher Fimbrmentioning
confidence: 99%